Highly efficient lignin removal from the waste liquor of chemical pulping with an integrated polyaluminium chloride-assisted acidification/activated carbon adsorption process. (10th September 2020) - Wang, Leiming; Shi, Haiqiang; Sun, Yanning; Hou, Minjie; Sheng, Xueru; Li, Na; Niu, Meihong
Abstract: To separate and utilize the saccharides from the waste liquor is an essential subject with significant economic and environmental benefits for wood bio-refinery of pre-hydrolysis kraft-based dissolving pulp production processing. However, the presence of lignin-derived substances makes this application still a quite challenging problem. In this paper, a novel process is proposed by integrating the polyaluminium chloride (PAC) -assisted acidification and activated carbon adsorption concepts to enhance the lignin removal from the premixed liquor of prehydrolysate and black liquor. The results show that 95.4% of acid-insoluble lignin (from 23.8 to 1.1 g/L) was removed by PAC-assisted acidification at a mild acidification of pH to 6.0 with the condition assisted by PAC concentration of 300 mg/L. This can dramatically reduce the acid consumption compared to traditional acidification when pH around 3.0 was required during the acidification of waste liquor to obtain higher lignin removal. After the removal of acid-insoluble lignin, 70.2% of acid-soluble lignin (from 10.4 to 3.1 g/L) can be removed by the treatment of optimized adsorption of activated carbon. Meanwhile, it was found that the presence of acid-insoluble lignin would deposit and block the pore structure on the activated carbon, thus affecting the further adsorption of acid-soluble lignin on the activated carbon. When the concentration of acid-insoluble lignin was over 1.5 g/L, this negative effect became very obvious, which was confirmed by the analysis of specific surface area and the observation of scanning electron microscope. This is an important, if not major, finding that will offer valuable reference on the optimization of acid soluble lignin removal by adsorption treatment in the future. Graphical abstract: Image 1 Highlights: Mixing the liquor of pre-hydrolysis and kraft pulping for utilization was proposed. PAC-assisted mild acidification induced an effective removal of acid-insoluble lignin. Effective removal of acid-soluble lignin can be achieved by adsorption of activated carbon. Acid-insoluble lignin seriously affects the adsorption capacity of activated carbon.